Supreme ultimate sexagenary cycle contribute activate human potential forecasting capacity - Nguyen, Ngọc Thạch (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The article presents the basic content of the new method of decoding the “Luc Hao Sutra”, improving forecasting accuracy, reducing gossipy, and enhancing detailed judgment, activate human forecast potential called the "Forecasting According to Supreme Ultimate Sexagenary Cycle" method. The article consists of 3 parts: Purpose and meaning of “Supreme Ultimate Sexagenary Cycle”; Theoretical basis; Some applications.